ANALYSIS OF STRENGTHENING RELIGIOUS LITERACY CULTURE IN PAI LEARNING (Case Study at Kertek Junior High School) - Gita Sista Indarsih; Maryono; Fatiatun (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Strengthening religious literacy culture is a strategic effort to improve literacy skills while shaping students' religious character. This study aims to analyze the implementation, strategies, and supporting and inhibiting factors in strengthening religious literacy in Islamic Religious Education learning at SMP Negeri 3 Kertek. This study uses a qualitative approach with field research, with data collection techniques through interviews, observation, and documentation, and analyzed using an interactive model. The results show that strengthening religious literacy is implemented through the integration of the School Literacy Movement and the Spiritual Improvement Activity Monitoring Program in the form of reading habits, joint prayers, tadarus, recitation of Asmaul Husana, and religious reflection in learning. The strategies implemented include habituation, integration in learning, the use of varied methods, as well as support from facilities and cooperation with parents. Supporting factors include school policies, infrastructure, and the active role of teachers, while inhibiting factors include low interest in reading, limited religious reading materials, and difficulties in student understanding. The implications of this study emphasize the importance of strengthening religious literacy that is designed systematically, innovatively, and sustainably to improve literacy skills and shape students' religious character